Vanillic Acid: A Comprehensive Review of its Chemistry, Biosynthesis, Biological Activities, Pharmacological Potential and Toxicological Profile (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Vanillic acid (VA), a naturally occurring phenolic acid, is widely present in plants and food sources. Its diverse pharmacological effects have attracted growing attention in recent years. Objectives: This review aims to comprehensively analyze the chemical structure, biosynthetic pathways, pharmacological properties, formulation strategies, safety profile, and therapeutic potential of vanillic acid. Methods: Extensive literature was reviewed covering preclinical studies, mechanistic evaluations, and formulation innovations involving vanillic acid. Information was gathered on its bioactivities, including antioxidant, anti-inflammatory, antidiabetic, neuroprotective, and wound-healing effects. Findings: VA exhibits a broad spectrum of pharmacological actions, acting primarily through modulation of oxidative stress, inflammatory mediators, and molecular pathways such as PI3K/Akt, NF-κB, and AMPK. Formulations like nanoparticles and hydrogels have enhanced its bioavailability and therapeutic efficacy. Toxicological studies confirm its safety, and it is recognized as GRAS in food contexts. Conclusion: Vanillic acid is a promising bioactive compound with multifunctional therapeutic properties and excellent safety. While preclinical evidence is robust, clinical trials are needed to validate its efficacy in human health applications.
Keywords: Antioxidant; Biosynthesis; Hydrogels; Nanoparticles; Phenolic acid; Vanillic acid